DISFEMISME PADA PEMBERITAAN KORUPSI DI MEDIA MASSA DARING - Reka Yuda Mahardika; Indra Nugrahayu Taufik (Jurnal Semantik, 2023)
This research is motivated by the increasing corruption in Indonesia. Meanwhile, the punishment applied is still not effective, so additional social punishment is needed in the mass media. The purpose of this study is to examine the various meanings and constructors that give rise to dysphemism in the online mass media Okezone.com. This study uses a descriptive semantic approach to 30 reports related to corruption. Based on the results of the analysis found 21 words and 51 phrases that can be categorized as dysphemism. This dysphemism can be seen in the limitation of views, marginalization, classification, cynicism, and sarcasm used to create a bad image for corruption and corruptors. Meanwhile, from a semantic perspective, at least four categorizations of meaning are found, namely denotative which is used for the purpose of describing corruption with its true meaning. The connotative meaning is used to include negative sense values. The meaning of the metaphor is used to compare corruption and corruptors with negative things. The meaning of euphemism is associated with corruption which has a negative image.